Handbook of railway vehicle dynamics - Iwnicki, S. 1962- (CRC/Taylor & Francis, 2006)
Understanding the dynamics of railway vehicles, and indeed of the entire vehicle-track system, is critical to ensuring safe and economical operation of modern railways. As the challenges of higher speed and higher loads with very high levels of safety require ever more innovative engineering solutions, better understanding of the technical issues and use of new computer based tools is required. Encompassing the field from historical development to state-of-the-art modeling and simulation methods, Simon Iwnicki's Handbook of Railway Vehicle Dynamics sets a new standard of authority and practica.
Keywords: Railroad cars -- Dynamics -- Handbooks, manuals, etc.; elektronické knihy; electronic books